Air pollution in a street canyon estimated considering different parameterisations of vehicle-induced turbulence - Mazzeo, Nicolas Antonio (2012)
Leeward air pollutant concentrations (C) are estimated by incorporating four parameterisations of traffic-produced turbulence (TPT) into the scaling of C inside a street canyon. Three parameterisations consider expressions previously introduced by other authors, based on a theoretical formulation of TPT and a semi-empirical approach already incorporated in an operational street model. The fourth scheme introduces an empirical expression of TPT derived from four full-scale street canyon datasets. Hourly NOx concentrations are calculated for an asymmetric street canyon in Buenos Aires, using meteorological observations at local airport and modelled background concentrations. Statistical indicators show that the performance of the four schemes is satisfactory.